Só mais um episódio avallando os efeitos do vício em Binge-watching, das motivações para assistir e das preferências por séries de TV na saúde mental - Pereira, Fernanda de Souza (2025)
With the significant increase in TV series consumption, studies have indicated relationships between excessive watching and various harms. Despite being a common practice and the associated problems, there is little scientific production on this topic in Brazil, which may be due to the lack of assessment tools. Therefore, the main objective of this dissertation is to evaluate the effects of binge-watching addiction, motivations for watching, and preferences for TV series on mental health. Study 1: This is an empirical study that aimed to adapt the Binge-Watching Addiction Questionnaire, the Watching TV Series Motives Questionnarie and the development of a TV Series Preference Scale to the Brazilian context. The sample consisted of 235 participants, with an average age of 28.8 years (SD = 8.91), the majority of whom were women (68.9%), single women (65.1%), university women students (29.4%), and women who both study and work (48.5%). The Confirmatory Factor Analysis of the BWAQ supported the four-factor second-order model explained by a first order factor, with satisfactory fit indices that (CFI = 0.988, TLI = 0.986, RMSEA = 0.058). The CFA of the WTSMQ showed an adequate fit of the interrelated four factor model (CFI = 0.988, TLI = 0.987, RMSEA = 0.073). In the Exploratory Factor Analysis of the TV Series Preference Scale, the KMO index (0.75) and the Bartlett sphericity test (1831.0, gl = 100, p < 0.001) that indicated a factorable correlation matrix. The Parallel Analysis indicated the extraction of five factors. Given the above, the present study was based on the importance of enabling measurement measures that enable the investigation of recent phenomena and enrich the discussion on the mental health. Study 2: This is an empirical study aimed at evaluating the effects of binge-watching addiction (BW), motivations for watching, and preferences for TV series on mental health. The study involved 254 participants (M = 28.2; SD = 9.88), most of whom were women (64.3%), single (76.5%), studying and working (49.8%), and had incomplete higher education (43.4%). The following tools were used: BWAQ, WTSMQ, Mini-DASS, Single-Item Sleep Quality Scale, and the Sociodemographic Questionnaire. Data was collected online via Google Forms. The study used SPSS and JASP for Pearson correlation analysis, ANOVA, and Path Analysis. The main results showed significant correlations between binge-watching addiction and mental health indicators, with anxiety having the highest coefficient (r = 0.43; p < 0.001). The escapism motivation showed the strongest correlation with negative mental health. ANOVA revealed that students had higher levels of binge-watching addiction (M = 33.64; p < 0.05). Path Analysis indicated that maladaptive motivations mediated the relationship between binge-watching addiction and mental health, with a significant indirect effect (λ = 0.45; p < 0.001). These findings suggest that binge-watching addiction is associated with negative mental health impacts, particularly when mediated by maladaptive motivations. Final Considerations: This study investigated the effects of binge-watching (BW) addiction, motivations for watching series, and preferences for genres on mental health, with significant contributions to psychology and media. The research revealed that maladaptive motivations, such as escapism and emotional stimulation, mediated the relationship between addiction and mental health. Limitations of the study include the representativeness of the sample, which was mainly composed of university students, making it difficult to generalize the results. Future directions suggest experimental studies with audiovisual stimuli to investigate the impact of specific content on BW engagement, exploring situational factors.